Pengaruh firm size, profitabilitas, leverage, dividend policy dan investment decision terhadap nilai perusahaan pada perusahaan sektor industrials di BEI periode tahun 2019-2023 - Nisrina, Jihan Arij; Hartono, Ulil (Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the effect of firm size, profitability, leverage, dividend policy, and investment decision on firm value in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The population of this study consists of 63 companies, with 42 companies selected as samples using purposive sampling. Data analysis was conducted using panel data regression. The results show that simultaneously, firm size, profitability, leverage, dividend policy, and investment decision have an effect on firm value. Partially, only dividend policy has a negative effect on firm value, while profitability, leverage, firm size, and investment decision have no significant effect. These findings indicate that a dividend policy that tends to distribute net income may be perceived negatively by investors, as it potentially reduces funds available for future investment and growth. Therefore, companies are advised to review their dividend policies and consider allocating more retained earnings for business development to enhance investor perceptions of the company’s growth prospects.